Bank advertisement in newspaper websites and the representative of gender / Noor Aileen Ibrahim ...[et al.] - Ibrahim, Noor Aileen; Mohd Noor, Nazirul Mubin; Anuar, Nuramira; Yusof, Ahmad Muhyuddin; Yusof, Nurul Kamalia; Ya Shak, Mohamad Syafiq; Mohamad Shah, Dianna Suzienna (Universiti Teknologi MARA, 2021)
Many individuals in the country are beset by financial woes and this has led most of them to search for information on the way to manage their finances. Many people read the newspapers especially online newspapers. Banks have often placed their advertisements using online news portals because it will easily reach various segments of the community. This paper is a study on bank advertisements in Bahasa Malaysia and English newspaper websites and the manner in which gender is represented in these advertisements. This study has found that there are stereotypical representation of women as being less successful than men whereas men are portrayed as more successful than the former. It is recommended that banks should change with the times and start acknowledging women as equally as successful in life and portray this image in their future advertisements as this will most probably attract more female clients to their financial institution.